On the (in-)stability and the endogeneity of the "normal" rate of capacity utilisation in a post-Keynesian/Kaleckian "monetary" distribution and growth model - Eckhard Hein (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2006)
In Kaleckian models of distribution and growth the equilibrium rate of capacity utilisation may persistently diverge from the normal rate' of utilisation. We assess this problem following the approach by Dumenil/Levy (1999) who consider the normal rate' of utilisation in a monetary production economy as the rate which is associated with price stability. Since inflation in our model is driven by distribution conflict, the normal rate' of utilisation is associated with consistent claims of firms and employees. Taking into account real debt effects of changes in inflation and distribution effects of monetary policy interventions we discuss the short-run stability of the normal rate' and address the issue of long-run endogeneity. Generally, we show that in a Kaleckian monetary distribution and growth model, which takes the major features of a credit economy seriously, the normal rate' of capacity utilisation is endogenous to distribution conflict and monetary policy intervention in the long run. And we also show that major Kaleckian results, in particular the paradox of costs, can be retained for the short and the long run.
urn:nbn:de:101:1-20080814138
Keywords: E12; E22; E25; E52; O42; 330; distribution; growth; capacity utilisation; inflation; monetary policy